Adapting to Change: Utilizing Assessment and Evaluation for Planning in Adult Education GED Programs - Karen Brinkley (Adult Education Research Conference, 2013)
When educational service programs are forced to adapt to mandates or other situational changes, assessment-based research can be a useful tool for identifying both challenges and opportunities relating to continued program success. This research demonstrates how programmatic needs assessments have been used in the context of the current General Education Development GED® exam and its upcoming changes.